Franco: a mind never at rest - Samuelson, Paul A. (PSL Quarterly Review, 2012)
In this article the author recounts some fond memories of Franco Modigliani. For depth, breadth, originality and Modigliani human wisdom gained in the ranking of scholars, the highest place of the twentieth century. Great Italian, great American economist, Franco was also one of the leading economists in the world. His students and employees outnumber those of Alfred Marshall and Vilfredo Pareto. JEL Codes: A11, B31, C1, C53, D0, E2, E3, E6